Uwagi na temat roli nauk przyrodniczych i nowej duchowości w ochronie przyrody - Kubiak, Adam B. (Studia Ecologiae et Bioethicae, 2009)
Issues of nature conservation, and socio-cultural movement called ecologism, are vivid becouse o f it’s many controvertions and actual validity in terms o f sustainable development. This paper presents contemporary motives o f preserving the nature, scientific ways of it’s realization, and chosen issues o f so called „ecological spirituality”. Reflection on the abilities and perils of science and spirituality, with reference to philosophy and practical conservation activity, will be led. Finally, there will be an attemption to answer the question about relation between nature preservation, science and ecological spirituality, and to define the spiritual condition and trends in contemporary ecologism.